(untitled) (Research, Society and Development, 2021)
Teleservice has gained ample space in Brazil through the advent of call centers, responsible for outsourcing the business sectors, generating a change in the interaction with customers through telephones. Thus, the voice often used in this type of work must be clear, as from the moment its production is characterized by an adequate intensity and projection, it causes an adequate vocal performance for professionals working in the telemarketing area. The objective of the research is to analyze the main benefits of speech therapy intervention in a call center. To substantiate the research, it was necessary to carry out an integrative literature review, analyzing theories about the correct use of professionals working in call centers. For the selection of research sources, the databases of Scielo, Pubmed and Capes were used, using sources produced between the years 2012 to 2021, with the search carried out between the months of August and October of the year 2021. By Through the research, it was possible to evidence several benefits of speech therapy for the health of call center professionals, emphasizing better ways of using the voice, thus avoiding coughing, hoarseness, among other problems.